Going Concern Audit Opinion on Manufacturing Companies in Indonesia - Meilda Wiguna; Hardi; Eka Hariyani (Politeknik Caltex Riau, 2021)
Going concern is important issue to be addressed since it determine how the business will survive. This study is entitled